2022
DOI: 10.35848/1882-0786/ac99b9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-induced polarity oscillation of superconducting diode effect

Abstract: Recently, an ultimate diode effect, a superconducting diode where an electric current shows the superconducting state in one direction and the normal state in the other direction, has been discovered in a noncentrosymmetric Nb/V/Ta superlattice. Here, we report that the polarity of the superconducting diode shows a sign reversal as a magnetic field is increased. Such a nonlinear behavior of the diode effect is beyond the phenomenology based on the Ginzburg-Landau theory. Based on a recent microscopic study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Here, the nonreciprocal critical current Ic, is defined as the difference between the critical current in the positive direction (Ic+) and that in the negative direction (Ic-). Figure 1 again above 0.375 T. This oscillating behavior of the nonreciprocal critical current is consistent with our previous report 20) .…”
Section: A D V a N C E P U B L I C A T I O Nsupporting
confidence: 92%
“…Here, the nonreciprocal critical current Ic, is defined as the difference between the critical current in the positive direction (Ic+) and that in the negative direction (Ic-). Figure 1 again above 0.375 T. This oscillating behavior of the nonreciprocal critical current is consistent with our previous report 20) .…”
Section: A D V a N C E P U B L I C A T I O Nsupporting
confidence: 92%
“…was ∼5% observed at 2 K. In addition, we have also observed that the Q-factor shows oscillatory behavior at some data points, which can be attributed to CGT magnetic domain reorientation or phase transitions of the finite-momentum pairing states [46]. Figure 4(c) shows the magnetization measurement of our CGT crystal for magnetic fields applied parallel to the ab-plane (black curve) and c-axis (red curve).…”
Section: Resultsmentioning
confidence: 70%
“…Fe/Pt-inserted non-centrosymmetric superconducting superlattices [[Nb(1.8 nm)/V(1.8 nm)/Ta(1.8 nm)] 3 /Nb(1.8 nm/V(0.9 nm)/ Pt(0.9 nm)/Fe(1.0 nm)/Pt(0.9 nm)/V(0.9 nm)/Ta(1.8 nm)]] 10 were fabricated by periodic insertion of symmetric Pt/Fe/Pt units into Nb/V/Ta superlattices [27][28][29][30] to control the Rashba superconductor [31] by altering the magnetization direction. X-ray diffraction (XRD)-based structural characterization confirmed that the constituent layers of superlattices were stacked as designed and exhibited the bcc structures with the (110) orientation (Figure S1a,b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%